2023
DOI: 10.3390/jcm12206603
|View full text |Cite
|
Sign up to set email alerts
|

Tick-Borne Encephalitis—Review of the Current Status

Malgorzata Kwasnik,
Jerzy Rola,
Wojciech Rozek

Abstract: The tick-borne encephalitis virus (TBEV) is the arboviral etiological agent of tick-borne encephalitis (TBE), considered to be one of the most important tick-borne viral diseases in Europe and Asia. In recent years, an increase in the incidence of TBE as well as an increasing geographical range of the disease have been noted. Despite the COVID-19 pandemic and the imposition of restrictions that it necessitated, the incidence of TBE is rising in more than half of the European countries analyzed in recent studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 107 publications
(128 reference statements)
0
5
0
Order By: Relevance
“…Moreover, in every year from 2005 onwards, the majority of cases had been diagnosed outside the traditional hotspot of Åland archipelago. These developments are not surprising considering that TBE has become more common at least in Europe and Asia and in Finland tick contact areas have expanded over the past 60 years with observations becoming more common also in eastern Finland [12][13][14][15]. The majority of previous studies have globally reported HSV as the most frequent viral pathogen, followed by VZV in several studies.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, in every year from 2005 onwards, the majority of cases had been diagnosed outside the traditional hotspot of Åland archipelago. These developments are not surprising considering that TBE has become more common at least in Europe and Asia and in Finland tick contact areas have expanded over the past 60 years with observations becoming more common also in eastern Finland [12][13][14][15]. The majority of previous studies have globally reported HSV as the most frequent viral pathogen, followed by VZV in several studies.…”
Section: Discussionmentioning
confidence: 95%
“…Lithuania, Latvia, and Estonia had the highest reporting rates [ 1 ]. The continuing increase in the number of TBEV strains detected in I. ricinus in Europe and the westward spread of I. persulcatus and the more virulent TBEV European and Siberian strains is of great concern [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the three main subtypes (European, Far Eastern, and Siberian), two other subtypes (Baikalian and Himalayan) have been described recently [ 4 ]. Tick Ixodes ricinus , mainly distributed in Europe, is the main vector for TBEV [ 5 ]. TBEV infections in humans mostly occur after the bite of an infected tick; however, the number of food-borne TBE infections occurring after consumption of unpasteurized goat milk has been increasing in recent years [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The techniques used to experimentally transmit HRTV in H. longicornis ticks could also be attempted using other ticks to help determine their potential for HRTV transmission, including I. scapularis and D. variabilis . In consideration of the fact that changing climactic conditions may foster further spread of tickborne HRTV, other global tick species capable of disease transmission could similarly be tested [ 51 , 52 , 53 ].…”
Section: Tick Infection Distribution and Rangementioning
confidence: 99%